REMODELING OF THE SMALL CALIBER CORONARY VESSELS IN EXPERIMENTAL ATHEROSCLEROSIS - Tryasak, N.S.; Silkina, Yu.V.; Klopotskіy, G.A.; Khudyakov, A.E. (World of Medicine and Biology, 2020)
Histological and morphometric studies of the small caliber coronary arteries’ structural rearrangement at different stages of atherosclerosis development in the experiment were performed. Atherosclerotic damage was modeled by administration of low-density human native lipoproteins to animals. Histological staining of the coronary arteries wall was carried out using hematoxylin-eosin, sudan III and the methods of Van Gieson and Malory. It was found that the degree of structural and morphometric changes in the small caliber coronary arteries depends on the term of the study. In the early stages after antigenic influence (6-11th week of the experiment), the initial signs of damage in the coronary arteries wall were observed. At the later stages (12–20th week of the experiment), the structural rearrangement of the small caliber coronary arteries was detected, which was characterized by a progressive statistically significant thickening of their wall by 38.7 %, due to narrowing of the lumen. The Vogenvort index increased by 2.3 times (p
Keywords: coronary arteries of small caliber; morphometry; atherosclerosis